Vector-Borne Disease Intelligence: Strategies to Deal with Disease Burden and Threats - Braks, Marieta; Medlock, Jolyon M.; Hubalek, Zdenek; Hjertqvist, Marika; Perrin, Yvon; Lancelot, Renaud; Duchyene, Els; Hendrickx, Guy; Stroo, Arjan; Heyman, Paul; Sprong, Hein (Frontiers in Public Health, 2014)
Owing to the complex nature of vector-borne diseases (VBDs), whereby monitoring of human case patients does not suffice, public health authorities experience challenges in surveillance and control of VBDs. Knowledge on the presence and distribution of vectors and the pathogens that they transmit is vital to the risk assessment process to permit effective early warning, surveillance, and control of VBDs. Upon accepting this reality, public health authorities face an ever-increasing range of possible surveillance targets and an associated prioritization process. Here, we propose a comprehensive approach that integrates three surveillance strategies: population-based surveillance, disease-based surveillance, and context-based surveillance for EU member states to tailor the best surveillance strategy for control of VBDs in their geographic region. By classifying the surveillance structure into five different contexts, we hope to provide guidance in optimizing surveillance efforts. Contextual surveillance strategies for VBDs entail combining organization and data collection approaches that result in disease intelligence rather than a preset static structure.